Tailoring Gelation Mechanisms for Advanced Hydrogel Applications. (18th August 2020) - Nele, Valeria; Wojciechowski, Jonathan P.; Armstrong, James P. K.; Stevens, Molly M.
Abstract: Hydrogels are one of the most commonly explored classes of biomaterials. Their chemical and structural versatility has enabled their use across a wide range of applications, including tissue engineering, drug delivery, and cell culture. Hydrogels form upon a sol–gel transition, which can be elicited by different triggers designed to enable precise control over hydrogelation kinetics and hydrogel structure. The chosen hydrogelation trigger and chemistry can have a profound effect on the success of the targeted application. In this Progress Report, a critical overview of recent advances in hydrogel design is presented, with a focus on the available strategies used to trigger the formation of hydrogel networks (e.g., temperature, light, ultrasound). These triggers are presented within a new classification system, and their suitability for six key hydrogel‐based applications is assessed. This Progress Report is intended to guide trigger selection for new hydrogel applications and inspire the rational design of new hydrogelation trigger mechanisms. Abstract : This Progress Report provides a critical overview of recent advances in hydrogel design, and focuses on the currently available approaches to trigger hydrogelation (e.g., temperature, pH, enzymes, light, ultrasound). These triggers are presented within a new classification system and illustrated with key examples and applications. Future opportunities are outlined to aid trigger selection and inspire the next generation of gelation mechanisms.